ISLAMIC DISCOURSE BETWEEN NATIONAL IDEOLOGY AND INDONESIAN LOCAL WISDOM (JOURNAL OF INDONESIAN ISLAM, 2010)
Islam has been understood differently by its adherents. Muslims from different intellectual currents of thought develop sharp difference in their interpretation of Islamic teachings. Muslims of Indonesia are not an exemption. In their effort to make Islam more acceptable in the local context, they have presented a form of Islam hardly found in another part of the Muslim world. This article is an attempt to make a contribution in what is called the “Indonesian version” of Islam. The article speaks of two kinds of Indonesian Islam, namely ideological and intellectual aspects.  The former is represented by the political currents aspired to “formalize” Islam as the state religion, while the latter is a pure academic movement aimed at “localizing” Islam in tune with the local values and norms. The paper tries to trace the deep reaches of these two forms of Indonesian Islam and delve into their internal dynamics. While it finds the idea of ideologising and localizing Islam to be originally Indonesian, the paper discovers that the contents of that idea are apparently imported.